Electron Backscatter Diffraction: An Important Tool for Analyses of Structure-Property Relationships in Thin-Film Solar Cells - Abou-Ras, D; Kavalakkatt, J; Nichterwitz, M; Schaefer, N; Harndt, S; Wilkinson, A; Tsyrulin, K; Schulz, H; Bauer, F (2013)
The present work gives an overview of the application of electron backscatter diffraction (EBSD) in the field of thin-film solar cells, which consist of stacks of polycrystalline layers on various rigid or flexible substrates. EBSD provides access to grain-size and local-orientation distributions, film textures, and grain-boundary types. By evaluation of the EBSD patterns within individual grains of the polycrystalline solar cell layers, microstrain distributions also can be obtained. These microstructural properties are of considerable interest for research and development of thin-film solar cells. Moreover, EBSD may be performed three-dimensionally, by alternating slicing of cross sections in a focused ion-beam machine and EBSD acquisition. To relate the microstructural properties to the electrical properties of individual layers as well as to the device performances of corresponding solar cells, EBSD can be combined with electron-beam-induced current and cathodoluminescence measurements and with various scanning-probe microscopy methods such as Kelvin-probe force, scanning spreading resistance, or scanning capacitance microscopy on identical specimen positions. Together with standard device characterization of thin-film solar cells, these scanning microscopy measurements provide the means for extensive analysis of structure-property relationships in solar-cell stacks with polycrystalline layers. © 2013 TMS.